ÁJINIYAZ SHÍǴARMALARÍNDA QOLLANÍLǴAN FOLKLORLÍQ DÁSTÚRLER - Qalbaeva, G.S. (SCIENCE and SOCIETY, 2025)
This article analyzes mythical motifs, details of the legendary plot and the processes of using images for artistic purposes, as well as traditional means of artistic representation used in the poetry of the poet Ajiniyaz to describe objects and events, create the image of a lyrical hero and express his romantic feelings.